El potencial de la nanotecnología para evitar que el SARS-Cov-2 ingrese a nuestro organismo. - Aphang Ly, Sylvia (2021)
We are in the midst of a global race against the COVID-19 pandemic, an infectious disease caused by the SARS-CoV-2 respiratory virus. In this context, nanotechnology represents an attractive alternative to fight the virus, due to its unique properties. This article presents a brief review of the differentnanotechnological tools developed for the inactivation of SARS-CoV-2 before it enters our organism, in personal protective equipment, inanimate surfaces and filter systems. A better comprehension of their mechanisms and the advantages they offer are key to a possible implementation in Peru.